2002
DOI: 10.1074/jbc.m209672200
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Potent and Orally Active Non-peptide C5a Receptor Antagonist

Abstract: The anaphylatoxin C5a is a potent chemotactic factor for neutrophils and other leukocytes, and functions as an important inflammatory mediator. Through a high capacity screening followed by chemical optimization,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
69
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(71 citation statements)
references
References 53 publications
(33 reference statements)
2
69
0
Order By: Relevance
“…As it has been shown that C5aRa (W54011) had no effect on the induction of Ca 2ϩ influx in mouse neutrophils (19) to further clarify W54011 has effect on DC functional modulation, we compared ϩ T cells. T cell proliferation was assessed by thymidine uptake at 72 h and IFN-␥ production was measured at day 5 by ELISA.…”
Section: Blockade Of C5ar Lowers DC Activation Phenotype and Allostimmentioning
confidence: 99%
“…As it has been shown that C5aRa (W54011) had no effect on the induction of Ca 2ϩ influx in mouse neutrophils (19) to further clarify W54011 has effect on DC functional modulation, we compared ϩ T cells. T cell proliferation was assessed by thymidine uptake at 72 h and IFN-␥ production was measured at day 5 by ELISA.…”
Section: Blockade Of C5ar Lowers DC Activation Phenotype and Allostimmentioning
confidence: 99%
“…Several antagonists for CD88 have been described, including peptides (20 -22), a nonpeptidic compound (23), C5a mutants (24 -26), and anti-C5aR antibodies (27,28). All of these compounds are potent CD88 antagonists in vitro; however, only the C5a mutants C5aRAM (24) and jun/fos-A8 (25), the cyclic peptide AcPhe[L-ornithinePro-D-cyclohexylalanine-Trp-Arg] (AcF-(OpdChaWR)) (29), and a nonpeptidic antagonist (23) have been proven useful in vivo. Administration of these inhibitors protects animals from in-flammatory responses in immune complex disease (25,29,30), ischemia/reperfusion injury (25,31,32), and C5a-induced neutropenia (23,24).…”
mentioning
confidence: 99%
“…All of these molecules are potent C5aRA for human CD88; however, only the C5a mutant jun/fos-A8 is also a potent antagonist for mouse, rat, and guinea pig CD88. C5aRAM acts as an antagonist for rabbit and micropig CD88 (24), AcF-(OpdChaWR) acts as an antagonist for rat and dog CD88 (29), and the nonpeptidic compound acts as an antagonist for gerbil and cynomolgus monkey CD88 (23).…”
mentioning
confidence: 99%
“…However, cellbased assays have reported that W-54011 is unable to block C5a-driven Ca 2+ mobilisation in polymorphonuclear leukocytesof rodents and select other mammals therefore it is possible that in vivo efficacy of this compound is unlikely (Sumichika et al, 2002). W-54011 is the only alternative small molecule C5ar1 antagonist commercially available therefore it was still deemed appropriate to test for in vivo efficacy to attempt to corroborate the in vitro results in a poorly understood in vivo disease situation.…”
Section: B Dmentioning
confidence: 99%
“…A summary adapted from Holland et al (2004) is given in Table 1 which outlines the animal models in which PMX53 has been tested. Additional compounds utilised in this thesis to modulate actions of C5ar1 not related to PMX53 in structure include the non-selective agonist EP54, which has been shown to also bind and activate C3ar, an anaphylatoxin receptor upstream in the complement cascade (Scully et al, 2010) and W-54011, an alternative non-peptide antagonist of C5a receptors (Sumichika et al, 2002).…”
Section: B Dmentioning
confidence: 99%